2019
DOI: 10.3390/en12071219
|View full text |Cite
|
Sign up to set email alerts
|

Historical Load Balance in Distribution Systems Using the Branch and Bound Algorithm

Abstract: One of the biggest problems with distribution systems correspond to the load unbalance created by power demand of customers. This becomes a difficult task to solve with conventional methods. Therefore, this paper uses integer linear programming and Branch and Bound algorithm to balance the loads in the three phases of the distribution system, employing stored data of power demand. Results show that the method helps to decrease the unbalance factor in more than 10%, by selecting the phase where a load should be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 16 publications
0
18
0
1
Order By: Relevance
“…From Formula (25) and from the other previous formulas, the magnitude of the APL depends on: the magnitude of root mean square value of the current and its frequency-the higher harmonic orders.…”
Section: Of 31mentioning
confidence: 98%
“…From Formula (25) and from the other previous formulas, the magnitude of the APL depends on: the magnitude of root mean square value of the current and its frequency-the higher harmonic orders.…”
Section: Of 31mentioning
confidence: 98%
“…Regarding the UC coefficient, the obtained value with the proposed algorithm is identical with AG (1.0017) at the SP level, being smaller than in the case of MCLA and PSO, as shown in Figure 13. Also, a comparison with the mathematical programming models, proposed by Arias et al in [4] and Zhu et al in [42], was done considering the UC coefficient. The UC coefficient was reduced from 1.17 to 1.07 (a reduction with 9.4%) using the Branch and Bound algorithm (BBA), proposed in [4], in the case of a test radial network without lateral branches.…”
Section: Consumer' Type Initial Phasementioning
confidence: 99%
“…The average value of the current in the neutral conductor, on the first branch, is shown in Figure 14, for each algorithm. It can be observed that the smallest value was obtained by applying the proposed algorithm (2.07 A), with 22.7% better than GA. Also, a comparison with the mathematical programming models, proposed by Arias et al in [4] and Zhu et al in [42], was done considering the UC coefficient. The UC coefficient was reduced from 1.17 to 1.07 (a reduction with 9.4%) using the Branch and Bound algorithm (BBA), proposed in [4], in the case of a test radial network without lateral branches.…”
Section: Consumer' Type Initial Phasementioning
confidence: 99%
See 2 more Smart Citations